Do Geographic Region, Pathologic Chronicity, and Hospital Affiliation Affect Access to Care Among Medicaid- and Privately Insured Foot and Ankle Surgery Patients?. Issue 1 (January 2021) - Pitts, Charles; McKissack, Haley; Alexander, Bradley; Jain, Mohit; He, Jun Kit; Jha, Aaradhana; Momaya, Amit; Shah, Ashish
Abstract : Objectives: Studies have shown that patients enrolled in Medicaid have difficulty obtaining access to care compared with patients with private insurance. Whether variables such as geographic location, state expansion versus nonexpansion, and private versus academic affiliation affect access to care among foot and ankle surgery patients enrolled in Medicaid has not been previously established. The purpose of this study was to assess the differences in access to care between patients who are privately insured and those with Medicaid in need of foot and ankle consultation. Secondary objectives include assessment of whether access to care for foot and ankle patients with Medicaid differs between those with acute and chronic conditions, Medicaid expanded and unexpanded states, geographic regions within the United States, and academic versus private practices. Methods: Twenty providers from each of five Medicaid-expanded and five nonexpanded states in different US geographic regions were randomly chosen via the American Orthopaedic Foot & Ankle Society directory. One investigator contacted each office requesting the earliest available appointment for their fictitious relative's acute Achilles tendon rupture or hallux valgus. Investigator insurance was stated to be Medicaid for half of the telephone calls and Blue Cross Blue Shield (BCBS) for the other half. Appointment success rate and average time to appointment were compared between private insurance and Medicaid. Results were further compared across geographic regions, between private and academic practices, and between urgent acute injury (Achilles rupture) and chronic nonurgent injury (hallux valgus). Results: Appointments were successful for all 100 (100%) calls made with BCBS as the insurer, in comparison to 73 of 100 calls (73%) with Medicaid ( P < 0.001). Both acute and chronic injury had significantly higher success rates with BCBS than Medicaid ( P < 0.001). The appointment success rate was significantly lower with Medicaid than with BCBS ( P ⩽ 0.01) in all of the geographic regions. The success rate with Medicaid (66.7%) was significantly lower than with BCBS (100.0%, P < 0.001) for private practice offices, but not for academic practices. Conclusions: Patients with Medicaid experience fewer options when obtaining appointments for common nonemergent foot and ankle problems and may experience less difficulty scheduling appointments at academic rather than private institutions. The medical community should continue to seek and identify potential interventions which can improve access to orthopedic care for all patients and increase the visibility of practices that accept Medicaid. Abstract : Medicaid is a federally and state-funded program established to provide health coverage to individuals in the United States who live beneath the federally determined poverty line. Studies have shown that patients enrolled in Medicaid have difficulty obtaining access to care compared with patients with private insurance. The purpose of this study was to assess the differences in access to care between patients who are privately insured and those with Medicaid in need of foot and ankle consultation. Secondary objectives include assessment of whether access to care for foot and ankle patients with Medicaid differs between those with acute and chronic conditions, Medicaid expanded and unexpanded states, geographic regions within the United States, and academic versus private practices.